The cellular architecture of the larval zebrafish tectum, as revealed by Gal4 enhancer trap lines - Scott, Ethan K.; Baier, Herwig (Frontiers in Neural Circuits, 2009)
We have carried out a Gal4 enhancer trap screen in zebrafish, and have generated 184 stable transgenic lines with interesting expression patterns throughout the nervous system. Of these, three display clear expression in the tectum, each with a distinguishable and stereotyped distribution of Gal4 expressing cells. Detailed morphological analysis of single cells, using a genetic “Golgi-like” labelling method, revealed four common cell types (superficial, periventricular, shallow periventricular, and radial glial), along with a range of other less common neurons. The shallow periventricular (PV) and a subset of the PV neurons are tectal efferent neurons that target various parts of the reticular formation. We find that it is specifically PV neurons with dendrites in the deep tectal neuropil that target the reticular formation. This indicates that these neurons receive the tectum's highly processed visual information (which is fed from the superficial retinorecipient layers), and relay it to premotor regions. Our results show that the larval tectum, both broadly and at the single cell level, strongly resembles a miniature version of its adult counterpart, and that it has all of the necessary anatomical characteristics to inform motor responses based on sensory input. We also demonstrate that mosaic expression of GFP in Gal4 enhancer trap lines can be used to describe the types and abundance of cells in an expression pattern, including the architectures of individual neurons. Such detailed anatomical descriptions will be an important part of future efforts to describe the functions of discrete tectal circuits in the generation of behavior.